An aerial survey of nesting Greater White-fronted and Canada Geese in west Greenland - Malecki, Richard A; Fox, Anthony D; Batt, Bruce D J (Wildfowl, 2000)
An aerial survey conducted in early June 1999 in west Greenland, between 62o and 72oN latitude, provided breeding pair estimates of 4,314 (+-785 SE) Greater White-fronted Geese (Anser albifrons flavirostris) and 2,631 (+-897 SE) Canada Geese (Branta canadensis). Only one pair of Canada Geese and no White-fronted Geese were observed on transects south of 66o 45' N. Mean densities of White-fronted (0.28 pairs/km2) and Canada Geese (0.25 pairs/km2), were highest in the Kangerlussuaq region (66o 55'-67o 30' N). North of this region, primarily in the area from 67o 30' N to the southern portion of Disko Bay (68o 40' N), densities declined to 0.11 pairs/km2 for White-fronted Geese and 0.03 pairs/km2 for Canada Geese. Few breeding pairs (<6, both species combined) were seen on transects north of the south Disko Bay region. However, increased snow cover and inclement weather prevented a full assessment of this more northerly region. At a local scale, the two species were less likely to occur together than expected by chance suggesting some spatial segregation. The importance of the Kangerlussuaq region to breeding Greater White-fronted Geese and the potential for competition with increasing numbers of recently established Canada Geese is discussed.